Adenocarcinoma of Ceruminous Glands: Role of the VMAT - Simona Vallarelli; Stefania Stucci; Marco Tucci; Nicola Quaranta; Donatella Russo; Marco Moschetta; Franco Silvestris (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Adenocarcinoma of the ceruminous glands is a rare malignancy arising from the glands of the external auditory canal. In most patients it is usually diagnosed as locally advanced disease with a major obstacle for radical surgery. Here, we describe two cases of patients suffering of sudden hearing loss and ipsilateral facial hemiparesis due to tumors arising from the ceruminous glands with primary intracranial involvement and subsequent middle ear infiltration. The patient with localadvanced disease underwent surgery followed by adjuvant treatment, whereas the other patient with advanced disease only to palliative therapy. However, both of them received volumetric-modulated arc radiotherapy (VMAT) resulting in complete remission as adjuvant treatment in the first patients while extending the survival as palliation in the second one. Thus, VMAT appears a suggested approach in this tumor which management is still poorly defined.